PENGGUNAAN STRATEGI GENIUS LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS SISWA PADA KELAS V SDN 028229 BINJAI BARAT - Suwondo, Haris; Ruslan, Dede; Yus, Anita (Jurnal Tematik, 2019)
"> This study aims to know the use of genius learning strategies to increase students’ motivation and social studies learning outcomes in the fifth grade of SDN 028229 West Binjai. This type of research is classroom action research (CAR). The results of this study are in the first cycle of students who succeeded as many as 10 people (40%) and students who have not completed as many as 15 people (60%) with an average score of 62.8. Students who have received good grades on aspects not quickly satisfied with the achievements that have been achieved amounted to 166 students with a percentage of 64%, it shows the level of student motivation is low. In the second cycle as a whole students complete 100% with an average value of 75.8. Some indicators that experienced an increase in motivation from the 14 existing indicators received a percentage of â‰¥80% and received a very good predicate. Thus the use of genius learning strategies can increase the motivation and results of social studies learning of students in class V SDN 028229 West Binjai